Pendampingan Dan Pelatihan Manajemen Administrasi PAUD - Masturoh, Umi; Wulandari, Fitrianti; Widyaningrum, Novita (PUDAK: Local Wisdom Community Journal, 2023)
This community service program aims to provide assistance and training in PAUD administrative management to all educational staff/treasurers in the PAUD Education Unit in the South Gresik region in Menganti District, Driyorejo District, Kedamean District and Wringinanom District. The focus on the PAUD administrative management mentoring and training program includes 1) sources of funds owned by PAUD units, 2) administrative management, 3) PAUD unit administration, 4) PAUD unit management reports, 5) obstacles to managing PAUD unit administration, 6) use of administration PAUD unit. Collection methods include interviews, observation, documentation, and direct observation in PAUD units. The implementation of mentoring activities and training on PAUD administrative management was carried out in 2 meetings and continued with consistent online mentoring. From the evaluation results, it was found that the use of administrative management of the PAUD units has been running well and in accordance with the procedures that have been jointly established at the annual meeting of each unit, however it is necessary to add additional educational staff or a treasurer if the principal of the PAUD education unit is also an operator, teachers, principals and also treasurers. Apart from that, educational staff belonging to the PAUD unit are given the opportunity to take part in seminars or training on improving the competency of financial managers to become more competent and professional treasurers.